2009
DOI: 10.1097/sla.0b013e31819255d0
|View full text |Cite
|
Sign up to set email alerts
|

Low Recurrence Rate After Laparoscopic (TEP) and Open (Lichtenstein) Inguinal Hernia Repair

Abstract: The recurrence rate for both TEP and Lichtenstein repair was low. A higher cumulative recurrence rate in the TEP group was seen at 5 years. Further analysis revealed that this could be attributable to incorrect surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 20 publications
3
94
1
5
Order By: Relevance
“…This finding is consistent with several studies [6][7][8][9]. Although some previous studies [4,10] showed that recurrence rates were higher among patients whose hernias were repaired by the laparoscopic technique, our study did not find such evidence.…”
Section: Discussionsupporting
confidence: 58%
“…This finding is consistent with several studies [6][7][8][9]. Although some previous studies [4,10] showed that recurrence rates were higher among patients whose hernias were repaired by the laparoscopic technique, our study did not find such evidence.…”
Section: Discussionsupporting
confidence: 58%
“…When performed by experienced surgeons, endoscopic inguinal hernia repair effectively reduces postoperative and chronic pain, is accompanied by fewer wound complications, and allows a shorter recovery time. Also, the recurrence rates for inguinal hernia are comparable with those for open techniques [3][4][5][6][7][8][9].…”
Section: Total Extraperitoneal Inguinal Hernia Repairsupporting
confidence: 51%
“…Increasing evidence has supported laparoscopic procedure as the ''gold standard'' treatment of choice in many surgical fields, especially for nonmalignant indications such as inguinal hernia repair [3,4]. At the beginning of the 1990s, laparoscopic hernia repair, including TEP and TAPP procedures, was controversial because the early recurrence rate was high [5].…”
Section: Discussionmentioning
confidence: 99%